Fundamentally Grounded [Gründlich mit Grund] - Elke Erb (Studies in 20th & 21st Century Literature, 1997)
Translated by James Rolleston et al. An East German poet examines her own production in the years 1991-1995. Precise images, e.g. of animals and landscapes both primeval and immediate, are correlated with the precise date and manner of their emergence from the poetic unconscious. The poet's self-questioning is autobiographical, professional, and social: What is the correlation between linguistic work and play and the ongoing transformation of a social order? What do intimate moments and enigmatic images tell us about the new realities of a capitalist collectivity? A key to the meaning of wrenching change is found in Erb's intensive involvement with the work of an older poet, Friederike Mayröcker.
Keywords: Translated; James Rolleston; East German poet; examines; production; 1991-1995; Precise images; image; animals; landscapes; primeval; immediate; poetic unconscious; poetry; unconscious; self-questioning; autobiographical; professional; social; linguistic; play; work; social order; intimate; time; capitalist; capitalist collectivity; Friederike Mayröcker; change